Phenotypic variation of thenus spp. (Decapoda, Scyllaridae) in the waters of southern thailand and malaysia using multivariate morphometric analysis - Ihsan Hani Radzi; Chen, Cheng Ann; Sukree Hajisamae; Kay Khine Soe (Instituto Oceanografico da Universidade de Sao Paulo, 2024)
Thenus spp. are slipper lobsters which are commercially significant as a food source with good aquaculture potential. This study focuses on collecting population information on Thenus orientalis and Thenus indicus from selected sites in southern Thailand and Malaysia to inform sustainable fisheries management about the resources. Twenty-five size-adjusted morphometric measurements were analyzed using canonical discriminant function and dendrogram cluster analyses to examine patterns of phenotypic variation between sites. Significant phenotypic variation with distinct centroids and minimal overlapping cases were observed among four sites of T. orientalis (p < 0.05), as well as cluster analysis groupings occurring as in (i) Kota Kinabalu and Kudat, in Sabah, Malaysia; (ii) Pattani; and (iii) Nakhon Si Thammarat, in Thailand, which were best discriminated by the width of the third pereiopod merus, the sixth abdomen segment, and the carapace posterior margin. Similar morphometric data between Kota Kinabalu and Kudat suggests a subpopulation of T. orientalis occurring in Sabah waters. Significant phenotypic variation was also detected between six sites of T. indicus (p < 0.05), with close centroids and overlapping cases forming three groups: (i) Ranong and Nakhon Si Thammarat; (ii) Kota Kinabalu, Tanjung Sedili, and Kuala Terengganu; and (iii) Pattani, best described by the widths of the second antenna and the first pereiopod merus, in addition to the length of the sixth abdomen segment. Cluster analysis shows the Pattani specimens clustering with the Malaysian specimens rather than the Thai specimens, suggesting homogeneous morphometric data between contiguous sites. Nakhon and Pattani forming separate groups in both species suggest discreet subpopulations occurring in the lower Gulf of Thailand. Patterns of phenotypic variation observed may be attributable to environmental conditions, local adaptations, and nomadic behavior. The findings can serve as baseline information for spatial planning in fisheries management, as well as to apprise regional efforts in the sustainable exploitation of Thenus spp.